ChemInform Abstract: A One‐Pot Approach to Δ2‐Isoxazolines from Ketones and Arylacetylenes. Issue 20 (25th April 2013) - Schmidt, Elena Yu.; Tatarinova, Inna V.; Ivanova, Elena V.; Zorina, Nadezhda V.; Ushakov, Igor' A.; Trofimov, Boris A.
Abstract The process involves at least five separate mechanistic steps: addition of ketones to arylacetylenes, oximation of the resulted β, γ‐unsaturated ketones, E→Z isomerization of the oximes (for oximes of alkyl‐ and cycloalkyl ketones), prototropic rearrangement of oximes of β, γ‐unsaturated ketones to oximes of α, β‐unsaturated ketones, and their final cyclization.